Design of a user-friendly and rapid DNA microarray assay for the authentication of ten important food fish species. (1st May 2020) - Kappel, Kristina; Eschbach, Erik; Fischer, Markus; Fritsche, Jan
Highlights: A DNA microarray assay was designed for the authentication of ten food fish species. The DNA chip featured 147 cytochrome b and 16S rDNA probes. The DNA chip was tested with PCR products of 67 different fish species. The probe signal pattern was specific for target species and closely related species. The colorimetric DNA chip assay takes four to five hours and is easy to use. Abstract: Seafood is particularly susceptible to the substitution of species. In order to guarantee authentic seafood products, seafood processors and traders must perform self-checks on the authenticity of imported and purchased goods. However, the conventional Sanger sequencing of PCR products for the authentication of seafood species is time-consuming and requires advanced infrastructure. DNA microarrays (DNA chips) with species-specific oligonucleotide probes represent a rapid alternative to sequencing-based species authentication. So far, though, only DNA microarrays for the authentication of land vertebrate species have achieved market success. In this work, a user-friendly DNA microarray assay was developed for the authentication of ten important food fish species that can be performed in four to five hours from start to end. The assay was tested with authenticated specimens from 67 different fish species, and by comparing the probe signal patterns all target species and even closely related non-target species could be distinguished.